Effect of inter-cluster interference on fracture morphology in multi-cluster staged fracturing for shale reservoir - Qingchao Li; Yuanfang Cheng; Dongxian Zhou; Qiang Li; Ubedullah Ansari (Fracture and Structural Integrity, 2018)
Multi-cluster staged fracturing technology is an effective measure to stimulate the reservoir properties. However, the inter-cluster interference effect is obvious when the cluster spacing is very narrow, which seriously affects the effect of fracturing. In order to understand the interference among fracturing clusters within the single fracturing section of the shale horizontal wells during multi-cluster staged fracturing, a finite element model is developed by using ABAQUS finite element simulation software. On this basis, the influences of factors on the fracture morphology are studied. The simulation results have shown that the cluster spacing is the most important factor affecting inter-cluster interference. With the increase in the distance between adjacent clusters, the interference among the fracturing fractures decreases and the propagation of different fractures become homogeneous or similar. Moreover, the increase in the elastic modulus of the shale formation promotes the propagation of the fractures longitudinally, but it hinders the crack opening of the fracture laterally. In addition, properly increasing the injection rate of fracturing fluid during fracturing is more advantageous for obtaining long and wide fractures. Besides, the effect of the fracturing fluid viscosity on fracture width is greater than that on the fracture half-length. The simulation results show the existence of inter-cluster interference comprehensively, which can provide a reference for the design and optimization of multi-cluster staged fracturing to some extent